A flexible laser ultrasound transducer for Lamb wave-based structural health monitoring. (26th May 2020) - Ding, Xiaoxi; Li, Wei; Xiong, Jitao; Shen, Yanfeng; Huang, Wenbin
Abstract: Lamb waves are widely used in structural health monitoring (SHM) for plate-like structures. In this paper, a new and flexible ultrasonic transducer with a high photo-acoustic conversion efficiency was proposed by using candle soot nanoparticles (CSNPs) and polydimethylsiloxane (PDMS). Experimental results demonstrate that the developed transducer can generate a longitudinal wave with a short duration of 0.28 μ s under the illumination of a nanosecond laser pulse. The amplitude of the excited longitudinal wave is 10 times that of the signal generated by the traditional laser ultrasound technique. Further, wedge-shape transducers were developed to excite Lamb waves in a 1.5-mm thick aluminum substrate by the oblique incidence method. The specific d A 0 and S 0 modes of the Lamb wave with the central frequency of 647 kHz were successfully excited in the aluminum plate. Based on the synthetic aperture focusing imaging technique, a delay-and-sum signal processing method was adopted for damage location in the plate by using the A0 mode Lamb. A 3.5-mm defect was well imaged and the results demonstrate that the developed flexible photo-acoustic transducer can be a good alternative method for SHM.